Correlation between urinary albumin to creatinine ratio and systemic glycocalyx degradation in pediatric sepsis (Medical Journal of Indonesia, 2018)
Background: Increased capillary permeability in sepsis is associated with several complications and worse outcomes. Glycocalyx degradation, marked by increased serum syndecan-1 levels, alters vascular permeability, which can manifest as albuminuria in the glomerulus. Therefore, elevated urinary albumin to creatinine ratio (ACR) potentially provides an index of systemic glycocalyx degradation. The aim of this study was to analyze the correlation between urinary ACR and serum syndecan-1 levels.Methods: A longitudinal prospective study with repeated cross-sectional design was conducted on children with sepsis in pediatric intensive care unit, we evaluated serum syndecan-1 levels and urinary ACR on days 1, 2, 3, and 7. A descriptive study on healthy children was also conducted to determine the reference value of syndecan-1 in children.Results: 49 subjects with sepsis were recruited. Based on the data of the healthy children group (n=30), syndecan-1 level of >90th percentile (41.42 ng/mL) was defined as systemic glycocalyx degradation. The correlation coefficients (r) between urinary ACR and syndecan-1 levels were 0.32 (p<0.001) from all examination days (162 specimens), 0.298 (p=0.038) on day 1, and 0.469 (p=0.002) on day 3. The area under the curve of urinary ACR and systemic glycocalyx degradation was 65.7% (95% CI 54.5%–77%; p=0.012). Urinary ACR ≥157.5 mg/g was determined as the cut-off point for glycocalyx degradation, with a sensitivity of 77.4% and a specificity of 48%.Conclusion: Urinary ACR showed a weak correlation with systemic glycocalyx degradation, indicating that the pathophysiology of elevated urinary ACR in sepsis is not merely related to glycocalyx degradation.